¿Somos iguales? Using a structural violence framework to understand gender and health inequities from an intersectional perspective in the Peruvian Amazon - Geordan D. Shannon; Angelica Motta; Carlos F. Cáceres; Jolene Skordis-Worrall; Diana Bowie; Audrey Prost (Global Health Action, 2017)
Background: In the Peruvian Amazon, historical events of colonization and political marginalization intersect with identities of ethnicity, class and geography in the construction of gender and health inequities. Gender-based inequalities can manifest in poor health outcomes via discriminatory practices, healthcare system imbalances, inequities in health research, and differential exposures and vulnerabilities to diseases. Structural violence is a comprehensive framework to explain the mechanisms by which social forces such as poverty, racism and gender inequity become embodied as individual experiences and health outcomes, and thus may be a useful tool in structuring an intersectional analysis of gender and health inequities in Amazonian Peru. Objective: The aim of this paper is to explore the intersection of gender inequities with other social inequalities in the production of health and disease in Peru’s Amazon using a structural violence approach. Design: Exploratory qualitative research was performed in two Loreto settings – urban Iquitos and the rural Lower Napo River region – between March and November 2015. This included participant observation with prolonged stays in the community, 46 semi-structured individual interviews and three group discussions. Thematic analysis was performed to identify emerging themes related to gender inequalities in health and healthcare and how these intersect with layered social disadvantages in the reproduction of health and illness. We employed a structural violence approach to construct an intersectional analysis of gender and health inequities in Amazonian Peru. Results: Our findings were arranged into five interrelated domains within a gender, structural violence and health model: gender as a symbolic institution, systemic gender-based violence, interpersonal violence, the social determinants of health, and other health outcomes. Each domain represents one aspect of the complex associations between gender, gender inequity and health. Through this model, we were able to explore: gender, health and intersectionality; structural violence; and to highlight particular local gender and health dynamics. Intersecting influences of poverty, ethnicity, geography and gender served as significant barriers to healthcare in both rural and urban settings.